Children's reading skills: The role of parental involvement in elementary school education - Roy Gustaf Tupen Ama; Rufina Nenitriana S Bete; Maria Regina Jaga (JURNAL SPIRITS, 2025)
Reading skills are fundamental to reading and must be possessed by students, especially elementary school students, as preparation for success in reading. The purpose of this study was to determine the effect of parents' perceptions of involvement on the reading skills of elementary school students. The research method used in this study was quantitative with statistical analysis. The research subjects in this study were elementary school students at Catholic School "X" in the Atambua area, East Nusa Tenggara (NTT). The research sample consisted of 40 students who met the research criteria. The research subjects were elementary school students in grades 4 and 5, both male and female, living with their parents, and already fluent in simple reading. The sampling technique used was purposive sampling based on specific characteristics. The research instruments used in this study were a scale of parental involvement perception and a reading skills scale. The data analysis technique in this study was a simple linear regression test. The results of the study showed a beta coefficient (B = 0.724), indicating a positive prediction of the influence of parental involvement perception on reading skills in elementary school students, with an F coefficient value (p = 0.001), so that the effective contribution of parental involvement perception to reading skills in elementary school students was 52.4%.